ARgot: Text-Based Detection Systems In Real Time Using Augmented Reality For Media Translator Aceh-Indonesia With Android-Based Smartphones - Ardian, Zalfie; Santoso, P. Insap; Hantono, Bimo Sunarfri (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
Language is a media of communication which aims to understand each ethnic and certain nation. The understanding of language allows the increase of awareness and closeness value among certain individuals. Nevertheless, considerable number of Languages appears to be the causes of difficulty and missunderstanding on the meaning of a certain word. This research suggests one of the solutions in solving such problem. Hence it eases Â the process of understanding the meaning of the words of a language. Especially âbahasa Acehâ. This aplication called ARgot. ARgot is an aplication of translation of Aceh â Indonesiaâs Language.Â  This aplication is able to work as real time application without having a need of an input media such as a text which has to type through using a good quality of camera and having characteristic of autofocus in camera. This research emphasizes on the process of detection and tracer text which availableÂ  withing the society. This research is also intended to see how the technology Augmented Reality is able to be applied in markerless text and have different font of variety.Â  The result Â of the research is a software for a android smartphone, as media translator in a real time, Hence it is able to be used almost in every kind of smartphone. Based on the trial and result of respondent, this aplication is able to attract the interest of user and it is also able to be aplied in a real life.Keywords: Augmented Reality, Translator, Text, Markerless